Accessible Elements: Teaching Science Online and at a Distance - Dietmar Kennepohl (Issues in Distance Education, 2010)
Accessible Elements informs science educators about current practices in online and distance education: distance-delivered methods for laboratory coursework, the requisite administrative and institutional aspects of online and distance teaching, and the relevant educational theory. Delivery of university-level courses through online and distance education is a method of providing equal access to students seeking post-secondary education. Distance delivery offers practical alternatives to traditional on-campus education for students limited by barriers such as classroom scheduling, physical location, finances, or job and family commitments. The growing recognition and acceptance of distance education, coupled with the rapidly increasing demand for accessibility and flexible delivery of courses, has made distance education a viable and popular option for many people to meet their science educational goals.